DOUGLAS HOWLAND, International Law and Japanese Sovereignty - Fisher, James C. (Zeitschrift für Japanisches Recht, 2017)
Douglas Howland International Law and Japanese Sovereignty. The Emerging Global Order in the 19th Century Palgrave Macmillan, London / New York 2016, XI, 232 pp., $105 ISBN: 978-1-137-56777-2